Community Capacity Strengthening for Covid-19 Disaster Prevention through the Independent Quarantine Installation - Paripurno, Eko Teguh; Wibowo, Elmi; Ashrianto, Panji Dwi; Mahojwala, Gandar (Universitas Sebelas Maret, 2020)
In Timbulharjo Village, Sewon District, Bantul Regency, Special Region of Yogyakarta, the Covid-19 pandemic has reached its fifth month. Individual citizens have economic limitations in preventing a pandemic. Refusal of migrants / refugees who need a place of independent isolation has the potential to increase conflict. These conditions make the installation of independent isolation and the accompanying empowerment program needed by community. This program helps solve citizens' problems. The program was built through collaborative community service and facilitation processes, thereby stimulating residents to realize other local initiatives in dealing with Covid-19. This dedication not only provides relief items, but also harmonizes local planning, management and resources that can be carried out independently by the community. Planning and implementation of the program is done on a multi-party basis (pentahelix). Citizens as subjects supported by the village government, educational institutions, business institutions, and the media. University of Pembangunan Nasipnal Veteran Yogyakarta represent educational institutions, in which there are Disaster Management Study Program, Disaster Management Study Centers, Covid-19 Task Force, UPN TV, and Alumni Association.